Doppler-Derived Intracoronary Physiology Indices Predict the Occurrence of Microvascular Injury and Microvascular Perfusion Deficits After Angiographically Successful Primary Percutaneous Coronary Intervention. (March 2015) - Teunissen, Paul F.A.; de Waard, Guus A.; Hollander, Maurits R.; Robbers, Lourens F.H.J.; Danad, Ibrahim; Biesbroek, P. Stefan; Amier, Raquel P.; Echavarría-Pinto, Mauro; Quirós, Alicia; Broyd, Christopher; Heymans, Martijn W.; Nijveldt, Robin; et al.
Abstract : Background—: A total of 40% to 50% of patients with ST-segment–elevation myocardial infarction develop microvascular injury (MVI) despite angiographically successful primary percutaneous coronary intervention (PCI). We investigated whether hyperemic microvascular resistance (HMR) immediately after angiographically successful PCI predicts MVI at cardiovascular magnetic resonance and reduced myocardial blood flow at positron emission tomography (PET). Methods and Results—: Sixty patients with ST-segment–elevation myocardial infarction were included in this prospective study. Immediately after successful PCI, intracoronary pressure–flow measurements were performed and analyzed off-line to calculate HMR and indices derived from the pressure–velocity loops, including pressure at zero flow. Cardiovascular magnetic resonance and H2 15 O PET imaging were performed 4 to 6 days after PCI. Using cardiovascular magnetic resonance, MVI was defined as a subendocardial recess of myocardium with low signal intensity within a gadolinium-enhanced area. Myocardial perfusion was quantified using H2 15 O PET. Reference HMR values were obtained in 16 stable patients undergoing coronary angiography. Complete data sets were available in 48 patients of which 24 developed MVI. Adequate pressure–velocity loops were obtained in 29 patients. HMR in the culprit artery in patients with MVI was significantly higher than in patients without MVI (MVI, 3.33±1.50 mm Hg/cm per second versus no MVI, 2.41±1.26 mm Hg/cm per second; P =0.03). MVI was associated with higher pressure at zero flow (45.68±13.16 versus 32.01±14.98 mm Hg; P =0.015). Multivariable analysis showed HMR to independently predict MVI ( P =0.04). The optimal cutoff value for HMR was 2.5 mm Hg/cm per second. High HMR was associated with decreased myocardial blood flow on PET (myocardial perfusion reserve <2.0, 3.18±1.42 mm Hg/cm per second versus myocardial perfusion reserve ≥2.0, 2.24±1.19 mm Hg/cm per second; P =0.04). Conclusions—: Doppler-flow–derived physiological indices of coronary resistance (HMR) and extravascular compression (pressure at zero flow) obtained immediately after successful primary PCI predict MVI and decreased PET myocardial blood flow. Clinical Trial Registration—: URL:http://www.trialregister.nl . Unique identifier: NTR3164. Abstract : Supplemental Digital Content is available in the text.